2018
DOI: 10.1097/md.0000000000010338
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ objective knowledge regarding venous thromboembolism prophylaxis

Abstract: Venous thromboembolism (VTE) is a common vascular disorder with high mortality and morbidity. Clinical nurses are a pivotal group that can serve as first-line health care providers. Lack of knowledge about VTE is an important barrier to effective nursing performance. This study aimed to determine nurses’ knowledge of VTE prophylaxis through a nationwide survey across China, to understand gaps between current knowledge, and guidelines, and to help improve clinical nursing.The survey included 5 topics with 68 it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 15 publications
1
36
1
5
Order By: Relevance
“…A enfermagem pode contribuir seja na avaliação de risco, orientação e administração medicamentosa, elaboração e implementação de protocolos de profilaxia como membro da equipe multidisciplinar (21) . Um estudo avaliou o conhecimento da equipe de enfermagem sobre profilaxia de TEV, o melhor domínio do conhecimento sobre tromboprofilaxia foi relacionado ao maior nível educacional, mais experiência e educação continuada, profissionais de terapia intensiva e enfermeiros líderes (22) . Há necessidade de fortalecimento da formação de enfermagem específica nessa área, que, consequentemente, contribuirá com abordagem direcionada e assertiva para prevenção de TEV (21) .…”
Section: Discussionunclassified
“…A enfermagem pode contribuir seja na avaliação de risco, orientação e administração medicamentosa, elaboração e implementação de protocolos de profilaxia como membro da equipe multidisciplinar (21) . Um estudo avaliou o conhecimento da equipe de enfermagem sobre profilaxia de TEV, o melhor domínio do conhecimento sobre tromboprofilaxia foi relacionado ao maior nível educacional, mais experiência e educação continuada, profissionais de terapia intensiva e enfermeiros líderes (22) . Há necessidade de fortalecimento da formação de enfermagem específica nessa área, que, consequentemente, contribuirá com abordagem direcionada e assertiva para prevenção de TEV (21) .…”
Section: Discussionunclassified
“…(12) Além de melhorar a autopercepção sobre o conhecimento, a educação continuada de enfermeiros se associa a maior conhecimento objetivo sobre tromboprofilaxia. (21) No entanto, embora o conhecimento percebido tenha sido predominantemente "bom" em nossa amostra, a proporção de respostas corretas às questões objetivas sobre TEV ficou abaixo de 60%, o que indica inadequado conhecimento objetivo. Essa discrepância pode ter acarretado a avaliação de risco de TEV pelos enfermeiros em apenas alguns pacientes.…”
Section: Discussionunclassified
“…[ 6 7 ] Unfortunately, previous research indicates that 10% of the patients with PE die because of the late diagnosis,[ 8 ] and one of its major risk factors increasing the occurrence of VTE is aging. [ 9 ] Others factors worldwide are the obesity epidemic and the aging population. [ 6 ] Another research is done in 2018 in China to assess the nurse’s knowledge about VTE and found that the more practiced, highly educated, lead nurses have better knowledge.…”
Section: Introductionmentioning
confidence: 99%